2006
DOI: 10.1103/physrevc.73.047601
|View full text |Cite
|
Sign up to set email alerts
|

ααdouble folding cluster potential description of theC12+

Abstract: We present a simultaneous analysis of the elastic scattering and fusion cross-section data of the 12 C + 24 Mg system around the Coulomb barrier and over energies by using the microscopic α-α double folding cluster potential within the framework of the optical model and the coupled-channels formalism. The α-α double folding cluster potential is obtained by using the α-cluster distribution densities of the nuclei in the usual double folding procedure. The microscopic potential results are compared with the find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…The numbers of neutrons and protons in the nucleus we study in this paper are integer multiples of those of an α particle, and such nuclei can demonstrate an α-cluster structure [25][26][27][28]. Therefore, it will be interesting to obtain the interaction potential by considering the α-particle structure of 16 O.…”
Section: B α-α Double-folding Cluster Potentialmentioning
confidence: 97%
“…The numbers of neutrons and protons in the nucleus we study in this paper are integer multiples of those of an α particle, and such nuclei can demonstrate an α-cluster structure [25][26][27][28]. Therefore, it will be interesting to obtain the interaction potential by considering the α-particle structure of 16 O.…”
Section: B α-α Double-folding Cluster Potentialmentioning
confidence: 97%
“…It has been shown that folding model potentials give a good account of the scattering between some 4N-type nuclei. For example, the 12 C+ 12 C, 16 28 Si elastic scattering data have been well described by folding potentials in diverse approaches [8][9][10][11][12][13][14][15][16]. However, for 16 O+ 20 Ne scattering, there is only one paper [17] involving a calculation using a folding potential; no other studies are available using a folding model to attempt to explain the 16 O+ 20 Ne scattering.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, many attempts have been made and published to reproduce these data using deep real potentials. To be able to reproduce the elastic and inelastic data, small additional derivatives were added to the deep real potential [24][25][26][27], or modified Ginocchio-type potentials were used [28].…”
Section: Introductionmentioning
confidence: 99%